Application of a novel percutaneous transluminal mitral commissurotomy technique in deformed mitral valve. (22nd June 2011) - Thomas, Tony; Ananthakrishna, Rajiv; Chikkabasavaiah, Nagamani Alur; Basavappa, Ramesh
Abstract : A 40-year-old woman, known to suffer from rheumatic heart disease, presented with New York Heart Association class III breathlessness of 6 months duration. Transthoracic echocardiogram revealed severe mitral stenosis with deformed double orifice–like mitral valve and severe interatrial septal bulge. Considering the unfavourable anatomy, a high-risk percutaneous transluminal mitral commissurotomy (PTMC) was planned. Initial septal puncture resulted in pericardial effusion with tamponade, which was effectively managed by pericardiocentesis. After haemodynamic stabilisation and a fresh septal puncture, repeated efforts were made to negotiate the balloon across the deformed valve using the conventional Inoue technique. As the attempts were unsuccessful, the authors planned for over-the-wire (OTW) technique, with which the procedure was accomplished successfully. A technically challenging case of PTMC in the presence of adverse factors is presented herein. OTW technique is a useful alternative in the presence of deformed mitral valve.